SISTEM PAKAR IDENTIFIKASI JENIS KULIT WAJAH DENGAN METODE CERTAINTY FACTOR - Yovita Kinanti Kumarahadi; M. Zainal Arifin; Sigit Pambudi; Tito Prabowo; Kusrini Kusrini (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2020)
The skin has many functions, including as a protective body, as a sense of touch or communication tools, and as a temperature regulator. The desire of most people, especially women, have white, healthy, clean and well-taken facial skin. However, the treatment does not pay attention to the type of skin, causing new problems such as acne, dry skin and others. To do skin care requires sufficient knowledge. This study aims to help provide identification of the type of facial skin using an expert system. The method used is certainty factor. The results obtained in this study are that this system has been able to identify the type of facial skin with an accuracy of 91%. Thus, an expert system for identifying the type of facial skin can be used to assist users in carrying out treatments.